1991
DOI: 10.1038/349340a0
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of tumorigenicity in human colon carcinoma cells by introduction of normal chromosome 5 or 18

Abstract: Development of colon carcinomas can be associated with allelic deletions on several chromosomes, including 5q and 18q. The APC gene on 5q and the DCC gene on 18q have been identified as potential tumour suppressor genes, whose suppression contributes to colon carcinogenesis. To investigate the role of genes in these deleted regions, we have now introduced a single normal human chromosome into a human colon carcinoma cell line, COKFu, through microcell hybridization. Several clones of hybrid cells containing no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
105
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(108 citation statements)
references
References 22 publications
3
105
0
Order By: Relevance
“…The strong prognostic value of 18q LOH for clinical course and survival of patients with CRC and the putative tumour-suppressive function of the DCC gene product (Tanaka et al, 1991) asks for the development of a method directly detecting the DCC gene product in CRC. As recently discovered by Hahn et al (1996), another putative tumour-suppressor gene, the DPC4 gene (deleted in pancreatic cancer locus 4), has been mapped to chromosome 18q21 very near to the DCC gene locus.…”
mentioning
confidence: 99%
“…The strong prognostic value of 18q LOH for clinical course and survival of patients with CRC and the putative tumour-suppressive function of the DCC gene product (Tanaka et al, 1991) asks for the development of a method directly detecting the DCC gene product in CRC. As recently discovered by Hahn et al (1996), another putative tumour-suppressor gene, the DPC4 gene (deleted in pancreatic cancer locus 4), has been mapped to chromosome 18q21 very near to the DCC gene locus.…”
mentioning
confidence: 99%
“…As shown in Figure 4, both DCC2 and DCC11 had slower growth kinetics characterized by a longer lag period after plating, and slower exponential growth rates as compared to parental HT29 and control Neo + cells. A decrease in growth kinetics has been reported in CoKFu cells transformed with the entire human chromosome 18, which harbors DCC (Tanaka et al, 1991).…”
Section: Expression a Ects The Growth Properties Of Ht29 Cellsmentioning
confidence: 93%
“…The introduction of chromosome 8p into colon cancer cell lines has been shown to decrease their tumourigenecity and invasiveness. 21 Furthermore, LOH at 8p has been shown to correlate with the presence of micrometastases. 22 Halling et al found that in stage II and III CRCs 8p allelic imbalance was an independent prognostic indicator for decreased survival and time to recurrence.…”
Section: Colorectal Cancer Biologymentioning
confidence: 99%